Afro-Arab relations : in the new world order - Chibwe, E. C. (London : Friedmann, 1977)
This book examines the trends towards increased Afro-Arab co-operation in the past few years, the success of recent negotiations and the need for a more detailed analysis of the needs of both areas.
Includes index.
usc 10/04/18
Loans
Keywords: International economic relations; Arab countries; Africa